Physico Chemical Analysis of Sapota (Manilkara zapota) Coated by Edible Aloe Vera Gel - Padmaja, N.; Don Bosco, S. John; Rao, J. Sudhakara (International Journal of Applied Sciences and Biotechnology, 2015)
The physical and chemical characteristics of the fruit have immense significance as they ultimately affect the quality of processed productsprepared from them. Over ripening of Sapota (Manilkara zapota) fruits at the post-harvest stage usually results in dramatic decline in quality.In the present study, physico chemical analysis (which includes Weight loss, Colour, Texture, TSS, pH, TA and Ascorbic acid content) ofedible Aloe vera gel coated Sapota fruits packed in LDPE and stored at 15 ± 2? were studied at regular intervals of 5 days i.e., 0th,5th, 10th,15thand 20th days. The dip treatment of Aloe vera gel coating 1:2, 7 minutes had best retained the physico chemical characteristics than the othertreatments performed and was found to be the most effective treatment in maintaining the fruit quality attributes along with the shelf lifeextension of about 20 days. DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.11703 Int J Appl Sci Biotechnol, Vol. 3(1): 20-25